SCHOOL UNDER TENSION: THE IMPACTS AND MEANINGS OF INFORMATION TECHNOLOGIES IN EDUCATION AND THE TRANSFORMATION OF CONTEMPORARY KNOWLEDGE - de Oliveira Neto, Francisco José (Seven Editora, 2026)
This chapter critically analyzes the integration of Information and Communication Technologies (ICTs) in the contemporary educational context, understanding them not only as technical tools, but as constitutive elements of culture, subjectivity, and teaching-learning processes. Starting from the understanding that we live in the age of connectivity, marked by the emergence of digital natives and immigrants, it discusses how technological transformations impact the ways of learning, teaching, and producing knowledge. Based on authors such as Castells, Lévy, Moran, Vygotsky, and Kerckhove, the chapter problematizes the institutional unease experienced by schools, historically organized to meet the demands of an industrial model, but now challenged to respond to the demands of a networked, dynamic, and hyperconnected society. It also analyzes the role of Brazilian public policies in the incorporation of ICTs into basic education and teacher training, highlighting their advances, tensions, and contradictions. Finally, this chapter proposes a reflection on the need to redefine pedagogical practices, teacher mediation, and the social function of the school in the face of the challenges posed by digital culture. DOI: https://doi.org/10.56238/sevened2026.004-006